Dynamic modelling and analysis of Organic Rankine Cycle power units for the recovery of waste heat from 110kW Proton Exchange Membrane Fuel cell system - Wilberforce, Tabbi; Muhammad, Imran (International Journal of Thermofluids, 2023)
•An integrated Organic Rankine Cycle (ORC) and PEMFC model is presented.•A developed PID controller is able to maintain the thermal efficiency of the ORC at 10%•The waste heat from the 110kW PEMFC is converted to 2.8kW power.•Optimization of the controller and mass flowrate of the working fluid increases power. The recovery of waste heat from Proton Exchange Membrane (PEM) Fuel cell is sin qua non to the development of organic Rankin cycle units. Despite the appreciable increase in the sale of PEM fuel cell units in 2021, the waste heat from some of these fuel cell units is typified by large fluctuations in mass flow rate as well as temperature which is more likely to affect the overall performance of an organic Rankine cycle (ORC) unit when coupled to a fuel cell. It is therefore imperative that the dynamic modelling of the Proton Exchange Membrane Fuel cell and organic Rankine cycle integrated system is developed to analyse the performance of the integrated system. This also involves the development of an appropriate control strategy for guaranteeing safer and optimum performance of the integrated system. The developed Proportional, Integral, Derivative (PID) control unit is able to maintain the thermal efficiency of the ORC system at 10% subject to the mass flow rate of the waste heat as well as the working fluid and also ensure safe operation of the integrated system. There is a 0.9% increase in the output power of the PEMFC after 2000 seconds of operation clearly highlighting the contribution of the integrated system in improving the overall output power being harnessed. [Display omitted]